Assessment of Clavicular Shortening in Displaced Midshaft Clavicular Fractures Treated by Nonoperative Method, Plating, and Elastic Nailing: Comparative Functional Analysis—A Case Series - Makesh Ram Sriraghavan; Poornima Kumararaja; Balakannan Jeyabalan (Journal of Orthopedics and Joint Surgery)
Introduction: Clavicular shortening can occur after midshaft clavicular fractures, and its impact on functional outcomes has been a subject of interest in orthopedic research. Some studies have reported that clavicular shortening is associated with worse functional effects, while others have not found a significant correlation. Our series aims to equate the outcomes between nonoperative management and surgical interventions using two different techniques—plating and elastic nailing. Materials and methods: A cohort of 60 patients with displaced middle-third fracture of clavicle managed by three procedures—nonoperative, elastic nailing, and plating each of 20 cases, respectively were reviewed after a mean follow-up of 2 years. The primary outcome variables were assessed. Results: The mean shortening observed was 1 ± 0.75 cm. Patients with clavicular length shortening of >2 cm had distinct differences in their clinical outcomes compared to patients with less severe shortening (<1 cm), as it's associated with discomfort or pain, which can negatively impact a patient's quality of life and functional ability. Severe shortening, greater than 2 cm, can result in functional impairment similar to nonunion. Those cases operated by elastic nailing have shortening of <0.5 mm, with plating of <0.75 cm. Conclusion: When the clavicle is shortened, it can alter the balance of muscles and ligaments around the shoulder joint, leading to functional impairment. The treatment choice is not solely based on fracture configuration but also considers other factors, including the patient's age, activity level, and the surgeon's judgment. There can be variations in the threshold for surgery among different surgeons and institutions. Elastic nailing to be used in displaced midshaft fractures and comminuted fractures plating is the ideal choice.